Literature, social media and questionnaire surveys identify relevant conservation areas for Carcharhinus species in the Mediterranean Sea. (January 2023) - Cattano, Carlo; Calò, Antonio; Aglieri, Giorgio; Cattano, Petra; Di Lorenzo, Manfredi; Grancagnolo, Desirèe; Lanzarone, Debora; Principato, Elena; Spatafora, Davide; Turco, Gabriele; Milazzo, Marco
Abstract: Sharks support ecosystems' health, but their populations are facing severe declines worldwide. Knowledge gaps on shark distribution and the negative human perception of them still represent a barrier to the implementation of effective conservation measures. Here we carried out a regional-scale analysis in the Mediterranean Sea using data on requiem shark catches and sightings available in the scientific literature and on social media platforms to: 1) depict the distribution of Carcharhinus species across the basin, 2) identify potentially relevant areas for their conservation, and 3) evaluate people's attitude toward shark protection. In addition, we administered 112 questionnaires in one of the very few shark-diving spots in the Mediterranean Sea to assess the potential role of sustainable shark-tourism activities in enhancing people's self-perceived knowledge of sharks and supporting positive attitudes toward their conservation. We show that social media content represented a valuable update of literature data from 58 papers contributing to identifying potentially relevant conservation areas for requiem shark populations. Social media data mining revealed a general shift toward positive perceptions of sharks in recent years, whilst negative attitudes still prevail in postings shared by fishers. Moreover, questionnaire surveys suggested that shark diving activities may further improve tourist perceptions of sharks and increase diver willingness to support conservation measures. By integrating different data sources, this study provides useful information for spatial conservation prioritization and for progressing our understanding of human and ecological dimensions of shark conservation, a necessary step toward specific and efficient protection policies.